Determinants of DMPA-SC self-care/self-injectable contraceptive uptake among modern contraceptive users in Burkina Faso: findings from the 2021 demographic and health survey - Bado, Aristide Romaric (Frontiers in Global Women's Health, 2024)
IntroductionThis study aimed to identify the determinants that influence the use of DMPA-SC/Sayana Press among women who use modern contraceptive methods in Burkina Faso.MethodsThis study used secondary data obtained from the 2021 Burkina Faso Demographic and Health Survey (EDSBF). The dependent variable is the use of DMPA-SC among women aged 15–49 who employ modern contraceptive methods. The descriptive analysis used percentages to describe the study variables. The Pearson chi-square test was used to assess the associations between the explanatory variables and the study variable of interest. Bivariate logistic regression was used to examine the crude odds ratios of each explanatory variable with respect to the dependent variable. The multivariate model was used to determine the net effect of each independent variable on the dependent variable. The significance levels were defined at p < 0.05, with corresponding confidence intervals.ResultsThe study revealed significant differences in the use of DMPA-SC according to age, marital status, region of residence, level of education, number of children, and involvement in contraceptive decision-making within the couple. Younger women (aged 15–29 aOR = 2.12, p < 0.001)) and women aged 30–39 (aOR = 1.51, p = 0.02) are also more likely to use DMPA-SC compared to those aged 40–49. Married women or those living with a partner [aOR = 1.93 (1.22, 3.05)] are more likely to use DMPA-SC. Women with 1–3 children are twice as likely to use DMPA-SC as those without children (aOR = 1.97, p = 0.02). Region and Wealth Index were significantly associated with DMPA-SC use. The Boucle du Mouhoun region showed a significantly higher likelihood of DMPA-SC use (aOR = 8.10) and women in the highest wealth group are significantly less likely to use DMPA-SC (aOR = 0.59, p = 0.001).ConclusionThese results demonstrated the importance of adapting interventions to account for socio-demographic, regional, and cultural differences. This will enable the provision of services to the entire female population in a fair and equitable manner, while also addressing the limitations and enhancing the understanding of the underlying factors influencing the use of DMPA-SC.